Six paths towards sustainability: a toolkit to promote a systemic transformation towards sustainable development in Finland - Furman, Eeva; Siivonen, Katriina; Linnanen, Lassi; Halme, Minna; Jaakkola, Jouni; Mönkkönen, Mikko; Saari, Juho; Salonen, Arto O.; Toivonen, Tuuli; Tolvanen, Anne; Soini, Katriina; Lyytimäki, Jari; et al. (Natural Resources Insitute Finland, Helsinki Institute of Sustainability Science, Finnish Environment Insititute, 2020)
The Global Sustainable Development Report shows that we are heading towards the sustainable development goals of Agenda 2030, but much too slowly. Inequality is increasing, climate change is advancing, biodiversity is decreasing, and waste volumes are growing. These phenomena are affected by several interconnected factors. However, we can change course if we identify the interlinkages between the aforementioned problems and steer our societies comprehensively in a more sustainable direction.
Keywords: sustainable development